Manajemen Sumber Daya Keluarga: Pelatihan Perencanaan Keuangan Dan Pembagian Peran Produktif Bagi Ibu Rumah Tangga Di Desa Sindangmukti - Ridwan Hakiki; Endang Syarif (CV. SINAR HOWUHOWU, 2026)
This community service activity aims to enhance economic resilience and the quality of family life in Sindangmukti Village through the implementation of character-based Human Resource Management (HRM). The primary challenges faced by the partners include low financial literacy, dependency on informal loans (local predatory lending or